Pengaruh Pelatihan, Disiplin Kerja, dan Komitmen Organisasi terhadap Kinerja Petugas Operasional (AVSEC, AMC, dan Terminal) di Bandar Udara Sultan Muhammad Salahuddin Bima - TinSafrina TinSafrina; Arif Fakhrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of training, work discipline, and organizational commitment on the performance of operational staff (AVSEC, AMC, and terminal staff) at Sultan Muhammad Salahuddin Bima Airport, both partially and simultaneously. The background of this study is based on the importance of human resources in supporting aviation security, safety, and operational efficiency, which necessitates optimal staff performance. The research subjects are all operational staff consisting of AVSEC, AMC, and terminal personnel at Sultan Muhammad Salahuddin Bima Airport, using a saturated sampling technique. The research method employed is a quantitative approach using a descriptive-associative method. Data collection was conducted through the distribution of a questionnaire that had been tested for validity and reliability. Data analysis utilized multiple linear regression, including partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results of the study indicate that: (1) training has a positive and significant effect on the performance of operational staff, with a significance level of 0.000 < 0.05; (2) work discipline has a positive and significant effect on the performance of operational staff, with a significance level of 0.000 < 0.05; (3) organizational commitment has a positive and significant effect on the performance of operational staff with a significance value of 0.000 < 0.05; (4) training, work discipline, and organizational commitment simultaneously have a significant effect on the performance of operational staff with a significance value of 0.000 < 0.05; and (5) the coefficient of determination of 78.1% indicates that the variables of training, work discipline, and organizational commitment contribute 78.1% to the performance of operational staff, while 21.9% is influenced by other variables outside the scope of this study.